2016
DOI: 10.3892/or.2016.5177
|View full text |Cite
|
Sign up to set email alerts
|

High expression of fibronectin is associated with poor prognosis, cell proliferation and malignancy via the NF-κB/p53-apoptosis signaling pathway in colorectal cancer

Abstract: Fibronectin is a glycoprotein of the extracellular matrix, and regulates the processes of self-renewal and cell cycle progression. This study aimed to investigate fibronectin expression in colorectal cancer (CRC) and elucidate the effects of fibronectin on CRC by using a knockdown approach. Immunohistochemistry was used to evaluate the expression of fibronectin in 107 CRC patient tissues and gene expression was detected by real-time quantitative PCR (qPCR) and western blot analysis. Based on the above findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 30 publications
1
54
1
Order By: Relevance
“…6C). Consistent with the previously reported patterns in breast, colorectal, and head and neck cancer types (21)(22)(23), these results suggest that fibronectin could serve as a robust prognostic marker across cancer types. As for correlations with established tumor subtypes, we found that many of the 258 protein markers were differentially expressed among the established tumor subtypes (e.g.…”
Section: S20supporting
confidence: 91%
“…6C). Consistent with the previously reported patterns in breast, colorectal, and head and neck cancer types (21)(22)(23), these results suggest that fibronectin could serve as a robust prognostic marker across cancer types. As for correlations with established tumor subtypes, we found that many of the 258 protein markers were differentially expressed among the established tumor subtypes (e.g.…”
Section: S20supporting
confidence: 91%
“…Noteworthy, specific modifications in FN structure are directly correlated to the onset of EMT. An illustrative example is that the expression of the FN splicing isoform EdB, specific for tumor tissues, is suggested to be a marker of EMT in translational oncology (Petrini et al, ; Yi et al, ).…”
Section: Ecm Remodeling During Carcinogenesismentioning
confidence: 99%
“…In CRC, NF‐κB is activated in cancer cells as well as in the surrounding microenvironment to sustain inflammation and promote proliferation, angiogenesis, invasion and eventually metastasis. Retrospective analysis indicated that activated NF‐κB is associated with tumor metastasis and poor prognosis . Thus, targeting the NF‐κB pathway has been an actively sought‐after strategy for novel anti‐CRC drug discovery, and a number of specific inhibitors have been developed for further clinical studies …”
Section: Introductionmentioning
confidence: 99%